2019
DOI: 10.21315/mjms2019.26.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Properties of Heterotrigona itama sp. Honey Via Induction of Apoptosis in Malignant Glioma Cells

Abstract: Background There has been increasing evidence showing that stingless bee honey exhibits anti-oxidant, anti-inflammatory and anti-cancer properties. Pharmacologically-active components in honey such as flavonoids and phenolic constituents are known to contribute to its medicinal benefits. To the best of our knowledge, this is the first study on evaluating anti-cancer effects of locally-produced Malaysian stingless bee honey from Heterotrigona itama sp. on malignant glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…At the same time, the increased interest in honey is argued, in particular, by its therapeutic properties [11] [12] [13], including wound healing [14], treatment gastric ulcer [15], in preventing and combating cancer [16] [17] [18], and other. The anti-inflammatory properties of bee honey reduce the severity of lung manifestations in COVID-19 infections, which is quite important in the current context [19] [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the increased interest in honey is argued, in particular, by its therapeutic properties [11] [12] [13], including wound healing [14], treatment gastric ulcer [15], in preventing and combating cancer [16] [17] [18], and other. The anti-inflammatory properties of bee honey reduce the severity of lung manifestations in COVID-19 infections, which is quite important in the current context [19] [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…By using cell proliferation and cells death assays, the authors demonstrated that SBH’s cytotoxic effect on this glioma cell line was time and dose-dependent. SBH also induced nuclear shrinkage, chromatin condensation and nucleus fragmentation, indicating that cellular changes were consistent with the apoptotic characteristics of the cells [ 33 ]. Taken together, these studies show exciting initial observations indicating that SBH may serve as a potential therapy for cancers and prompts the need for further investigation.…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…The results showed that SBH added to the culture media for three days resulted in a dose-dependent proliferative effect on DPSCs [ 35 ]. Another recent study by Ahmad et al has evaluated anticancer effects of SBH on malignant glioma (U-87) cells [ 33 ]. By using cell proliferation and cells death assays, the authors demonstrated that SBH’s cytotoxic effect on this glioma cell line was time and dose-dependent.…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…Glioma Cells, 2019 38 Esse trabalho demonstrou atividades anticâncer promissoras do mel de abelha sem ferrão da Malásia (Heterotrigona itama sp.) via inibição da proliferação de células e indução de apoptose precoce em linhagens de células de glioma maligno.…”
Section: Anti-cancer Properties Of Heterotrigona Itama Sp Honey Via Induction Of Apoptosis In Malignantunclassified